Initiating Green Waqf Finance in Waqf Forests: A Sharia-Based Financing Model for the Sustainability of the People's Economy, Ecology, and Ecosystems - Yuli Yanti Wulansari; Wahyu Ari Andriyanto; Dewi Agustya Ningrum; Nabila Mirza Syifd; Muhammad Arif Billae (Universitas 17 Agustus 1945 Surabaya, 2026)
This research aims to develop a financing model for waqf forest management based on Sharia accounting to support economic, ecological, and ecosystem sustainability. The use of waqf in Islam has evolved from a consumptive function to a productive social financial instrument. In this research, waqf forests are a strategic innovation that not only has ecological value but also has the potential to provide sustainable economic benefits to the community. However, a structured financing model that complies with Sharia accounting principles is not yet available, even though financial transparency and accountability are crucial for managing natural resource-based waqf. This research proposes the development of a Green Waqf Finance Model, a waqf financing scheme that integrates Sharia accounting standards (PSAK 112 and AAOIFI), the principles of maqasid sharia, and a green finance approach. Using exploratory qualitative methods and a case study of the waqf forest in Ngembat Village, Mojokerto, this research explores actual practices, formulates relevant accounting principles, and develops a waqf reporting framework that integrates spiritual, economic, social, and ecological dimensions. The novelty of this research lies in the rarely researched subject of waqf forests, the integration of the triple bottom line in waqf reporting, and its contribution to the Sustainable Development Goals (SDGs) agenda. The final results are expected to serve as academic and practical references for waqf managers, regulators, and Islamic financial institutions in developing fair, transparent, and sustainable financing systems.